2005
DOI: 10.1016/j.febslet.2005.03.094
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative imbalance and cathepsin D changes as peripheral blood biomarkers of Alzheimer disease: A pilot study

Abstract: Markers of oxidative stress in peripheral blood from patients with Alzheimer disease (AD) were analyzed. Thirtythree AD patients were recruited. Plasma antioxidant power (AOP), plasma Cystatin C as well as Cathepsin D in PBL were evaluated. We found that the AOP levels were significantly decreased in AD patients if compared to healthy donors, while the plasma level of Cystatin C was significantly higher. Importantly, a significantly decreased expression of Cathepsin D in PBL was also observed. These results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 52 publications
3
34
0
Order By: Relevance
“…Patients with high serum CysC level indicated a onefold higher risk of DPN. As mentioned earlier, CysC was proved to be related to both CNS and peripheral nervous system diseases in several observational studies (13). Consistent with that, we found a significant increase in serum CysC levels in type 2 diabetic DPN patients.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Patients with high serum CysC level indicated a onefold higher risk of DPN. As mentioned earlier, CysC was proved to be related to both CNS and peripheral nervous system diseases in several observational studies (13). Consistent with that, we found a significant increase in serum CysC levels in type 2 diabetic DPN patients.…”
Section: Discussionsupporting
confidence: 79%
“…It has been proved that CysC regulated the aggregation and deposition of amyloid b (12). And the serum CysC levels in patients with Alzheimer's disease were found be significantly higher than healthy controls (13). Moreover, change in the concentration of CysC in cerebrospinal fluid was also observed in demyelinating diseases including multiple sclerosis and Guillain Barre syndrome.…”
Section: Introductionmentioning
confidence: 83%
“…This suggests that the fragment is generated via an alternative, non-amyloidogenic processing pathway. While definitive identification of this fragment will require isolation and amino acid sequencing, it has previously been reported that the activity of cathepsin D is decreased in the blood of AD subjects (Straface et al, 2005). Cathepsin D is an aspartyl protease that cleaves APP at a number of different sites (Higaki et al, 1996), including at Ser627, Phe765, Glu766, and Met768.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the search for anomalous levels of free radical products facilitates the selection of biomarkers in AD. Several studies have shown that free radical products are present in the cerebrospinal fluid (CSF) of AD patients (Montine et al, 2002, Praticò et al, 1998, Strafacea et al, 2005. Nevertheless, CSF is not routinely collected in the evaluation of AD, and lumbar puncture is not a widespread procedure.…”
Section: Introductionmentioning
confidence: 99%